The Little Prince [Malý princ anglicky] - Saint-Exupéry, Antoine de, 1900-1944 (Best of children´s classics, 2022)
"All grown-ups were once children... but only few of them remember it." Now with the restored original artwork, the beloved classic story of a young prince's travels throughout spacea profound tale about loneliness and loss, and love and friendship.A pilot crashes in the Sahara Desert and encounters a strange young boy who calls himself the Little Prince. The Little Prince has traveled there from his home on a lonely, distant asteroid with a single rose. The story that follows is a beautiful and at times heartbreaking meditation on human nature.The Little Prince is one of the best-selling and the 4th most translated book of all time, universally cherished by children and adults alike, and Richard Howard's translation of the beloved classic beautifully reflects Saint-Exupéry's unique and gifted style, bringing the English text as close as possible to the French in language, style, and spirit. In this special edition, the artwork has been restored to match in detail and in color Saint-Exupéry's original artwork.This definitive English-language edition of The Little Prince will capture the hearts of readers of all ages.